2018
DOI: 10.1093/bjsw/bcy093
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Reintegration Support: The Dual Perspectives of Returnees and Caseworkers

Abstract: Many European countries have developed assisted voluntary return and reintegration (AVRR) programmes to support the return and reintegration of migrants who do not have a legal residence permit. There is substantial involvement of social-care professionals in the implementation of these programmes. However, the contested nature of AVRR programmes has limited an in-depth understanding of the exact nature of reintegration support and the ways it affects migrants’ lives after return. Through exploring the usefuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…55 Sulfur also is such an element known to increase the amount of pearlite in malleable irons, 56 lamellar irons, 57 compacted and nodular irons. 58 Nakae 59 and Ying Zou 60 demonstrated that a S-free lamellar cast iron is fully ferritic when a common lamellar iron would be nearly fully pearlitic for the same casting conditions. Assuming S adsorbs preferentially on basal planes in solid state as concluded for solidification, this would mean it hinders the formation of new graphite steps on top of the existing basal planes, thus hindering the development of new prismatic faces where carbon atoms could reach graphite precipitates.…”
Section: Solid-state Transformationsmentioning
confidence: 99%
“…55 Sulfur also is such an element known to increase the amount of pearlite in malleable irons, 56 lamellar irons, 57 compacted and nodular irons. 58 Nakae 59 and Ying Zou 60 demonstrated that a S-free lamellar cast iron is fully ferritic when a common lamellar iron would be nearly fully pearlitic for the same casting conditions. Assuming S adsorbs preferentially on basal planes in solid state as concluded for solidification, this would mean it hinders the formation of new graphite steps on top of the existing basal planes, thus hindering the development of new prismatic faces where carbon atoms could reach graphite precipitates.…”
Section: Solid-state Transformationsmentioning
confidence: 99%
“…Moreover, given the diverging interests and priorities involved in assisted return (Lietaert, 2019), an open category of post-return well-being might also provide an interesting discursive tool to scrutinize post-return situations (Atkinson and Joyce, 2011). On the micro-level, discussions and negotiation between returnees and counsellors on how individual reintegration assistance can be mobilized to contribute to post-return well-being might be a promising avenue to truly realize the "tailor-made" approach these programmes aim for.…”
Section: Discussionmentioning
confidence: 99%
“…On the micro‐level, discussions and negotiation between returnees and counsellors on how individual reintegration assistance can be mobilized to contribute to post‐return well‐being might be a promising avenue to truly realize the “tailor‐made” approach these programmes aim for. This, however, requires sufficient flexibility to be built into these programmes to enable adaption of the support to specific contexts, needs and priorities (Kuschminder, 2017b; Lietaert, 2019). On the policy level, Atkinson and Joyce (2011) argue that discussions on the content and meaning of well‐being as valuable, as it stimulates critical debate about the nature of overarching policy goals, such as reintegration, and enables strategies to be negotiated and reconciled locally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the highly influential context of return is also missing for this group, as well as any focus on reducing differences between returnees and those who stayed. This results in a strong individualizing approach to the complex social issue of reintegration for this group, which alleviates the state's responsibility for addressing structural barriers (Sinatti, ) and, accordingly, depoliticizes the problems faced by these returnees (Lietaert, ).…”
Section: The “Succesful” Re‐entry Of Refugees and Asylum Seekersmentioning
confidence: 99%